Um olhar sobre o abrigamento: a importância das histórias infantis em contexto de abrigo - Carvalho, Cíntia (2008)
Comprehending the complex universe of the child that lives in the context of a shelter, upon the eyes of diverse social actors made up the goal of the present research. Semi structured interviews were performed with the technical staff of the institution who included the manager, social worker and secretary as well as four professionals responsible for the care of the children in the home houses known as social mothers and two employees who were responsible for substituting the social mothers when they did not come to work known as substitutes. Interviews furnished important subsidies for the comprehension of aspects that involved the reality of the sheltered child, as follows: concepts of the technical staff and workers upon the child in this context as well as aspects regarding the development and learning of the children; concepts on the family of origin and relevant aspects of bonding situations in the institutional context. Considering that the child is one of these social actors, potent and able to express him/herself, story workshops, that sought, through fairy tales, to bring out narratives in the sheltered children, were performed in three groups of children from 5 (five) to 7 (seven) years old. Seeking strategies to improve the research performed with the children, small groups were chosen as to provide a space for conversation and expression of subjectivity toward their classmates. Nine workshops were performed with group 1 (7 years), nine with group 2 (6 years), and seven with group 3 (5 years). Diverse scholars of fairy tales were used and in the context of constructed stories featured by children, Jerome Bruner, who believed that fairy tales were important for the construction of the narrative thinking, was priority. Initially children appeared to be distant to the universe of fairies, dreams, fantasies so adult like due to their experiences, however it was possible to perceive that besides contributing for the narrative construction, the fairy tales made possible the expressions of daily experiences and was capable of redeeming childhood fantasy if they had been experienced by the narrator as true and appropriated, which can be determined by the experience and situations that involved the children.